2015
DOI: 10.3892/ol.2015.3414
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity affects EGFR and KRAS gene alterations of lung adenocarcinoma

Abstract: Abstract. Mutations or copy number gains (CNGs) of the EGFR and KRAS genes are representative alterations in lung adenocarcinomas that are individually associated with patient characteristics such as ethnicity, smoking status and gender. However, the effects of combinations of these genetic alterations have not been statistically examined. The present study analyzed previously examined lung adenocarcinoma cases in Asian (n=166) and non-Asian (n=136) individuals in whom all four EGFR and KRAS alterations had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…5 It has been proposed that ethnicity may explain these differences. 6,7 To investigate the potential role of interethnic genetic variation in the etiology of EGFR-mutant lung cancer, we analyzed the relationship between two genetic biomarkers of East Asian ancestry and the frequency of EGFR mutations in patients with lung adenocarcinoma in a range of countries.…”
Section: Introductionmentioning
confidence: 99%
“…5 It has been proposed that ethnicity may explain these differences. 6,7 To investigate the potential role of interethnic genetic variation in the etiology of EGFR-mutant lung cancer, we analyzed the relationship between two genetic biomarkers of East Asian ancestry and the frequency of EGFR mutations in patients with lung adenocarcinoma in a range of countries.…”
Section: Introductionmentioning
confidence: 99%
“…2 Since precision medicine is driven by data that primarily represents non-Hispanic white (NHW) patients, there is a significant potential health disparity for under-represented groups. 36 Non-small cell lung cancer (NSCLC), is the leading cause of cancer death among H/L men and second only to breast cancer in H/L women. 3 In NHW individuals, half of NSCLC cases have been shown to possess at least one of several known driver mutations, including alterations in KRAS, EGFR, MET, HER2, BRAF, PIK3CA, AKT1, MAP2K1, ALK, and MEK.…”
Section: Introductionmentioning
confidence: 99%
“…All of the patients in this study were from Chinese populations, and the rate of EGFR mutation in lung adenocarcinoma is different between ethnic groups. It has been reported that EGFR mutation rates in Asian patients are higher than in Westerners, at rates of 50% and 20%, respectively . As such, our prognostic model may be more suitable to Asian patients.…”
Section: Discussionmentioning
confidence: 83%
“…It has been reported that EGFR mutation rates in Asian patients are higher than in Westerners, at rates of 50% and 20%, respectively. 27,28 As such, our prognostic model may be more suitable to Asian patients. Finally, we used two kinds of test methods that might have different positive detectable rates of EGFR mutations.…”
Section: Discussionmentioning
confidence: 97%